Passport to profit a guide to global investing - Mobius, Mark (Orion Business, 1999)
This text shows the average person how best to invest abroad, how to devise a global investment strategy, and the pros and cons of buying individual stocks or mutual funds. There is also an analysis of the current crisis facing Asia, and what the future global marketplace will look like.